PANDANGAN TOKOH NAHDLATUL ULAMA DAN MUHAMMADIYAH KABUPATEN KUDUS TERHADAP FENOMENA SUAMI YANG MELALAIKAN KEWAJIBAN NAFKAH SEBAGAI BENTUK BAKTI KEPADA ORANG TUA - Muhammad Irvan Zidni Al Hakim; Masrokhin Masrokhin (JOURNAL SAINS STUDENT RESEARCH, 2025)
This thesis aims to answer the problem of how Nahdlatul Ulama and Muhammadiyah figures in Kudus Regency view the phenomenon of husbands who neglect their obligations to provide sustenance as a form of devotion to their parents. This thesis uses a type of empirical legal research which is a legal research method by examining applicable legal provisions in the form of Islamic law and what happens in reality in society. The results of this study concluded that: first, the husband's actions neglecting his obligations as head of the family are negligence in terms of sustenance, by acting unfairly to his wife regarding the level of sustenance given, namely his parents get a higher level than his wife so that his small family experiences a shortage in meeting daily needs. Second, the husband's actions are not justified even though the reason is to be given to his parents. So in carrying out these obligations, do not neglect other obligations, namely providing for your wife. Because Islam is a religion that emphasizes and upholds justice in every aspect of life